Taming the parent oxoborane - Kundu, Gargi; Amrutha, P. R.; Raj, K. Vipin; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Chemical Science, 2023)
Despite recent advancements in the chemistry of multiply bound boron compounds, the laboratory isolation of the parent oxoborane moiety, HBO has long remained an unsolved and well-recognized challenge. The reaction of 6-SIDipp(.)BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl)tetrahydropyrimidine2-ylidene] with GaCl3 afforded an unusual boron-gallium 3c-2e compound (1). The addition of water to 1 resulted in the release of H-2 and the formation of a rare acid stabilized neutral parent oxoborane, LB(H)]O (2). Crystallographic and density functional theory (DFT) analyses support the presence of a terminal B=O double bond. Subsequent addition of another equivalent of water molecule led to hydrolysis of the B-H bond to the B-OH bond, but the `B=O' moiety remained intact, resulting in the formation of the hydroxy oxoborane compound (3), which can be classified as a monomeric form of metaboric acid.

Access to NHC-Boryl mono- and bis-selenide and utility as mild selenium transfer reagent including to the C-F bond - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (Chemistry- a european journal, 2024)
Reactions of 5-SIDipp & sdot; BH3 (5-SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene) (1) with diphenyldiselenide provide access to 5-SIDipp-boryl mono- (5-SIDipp & sdot; BH2SePh) (2) and bis-selenide (5-SIDipp & sdot; BH(SePh)2) (3). The facile cleavage of the B-Se bond makes 2 a neutral source of selenium nucleophiles in substitutions reactions with benzyl bromides, and provide access to the corresponding selenoethers. The direct transformations of one of the C(sp2)-F bonds of C5F5N and C6F5CF3 to C-Se bonds have also been achieved by the use of 2 without employing transition-metal catalysts. While it was previously established that C6F6 could undergo complete defluoroselenation under harsh conditions, we successfully achieved partial defluorination of C6F6 by employing 2 as a mild selenide transfer reagent. During the formation of C-Se bonds through the cleavage of C-F bonds, the potential by-product NHC & sdot; BH2F undergoes ring expansion of the NHC, leading to the formation of the six-membered diaazafluoroborinane (7). Access to NHC & sdot; boryl mono- and bis-selenides from NHC & sdot; BH3 has been achieved. The boryl mono selenide has been demonstrated to function as a selenium transfer reagent, enabling the synthesis of selenoethers from benzyl bromide. Additionally, it can also facilitate the conversion of the challenging aromatic C-F bond to a C-Se bond, resulting in concomitant ring expansion of NHC & sdot; haloborane.image
Keywords: boron; C-F Bond Activation; N-Heterocyclic carbene; Ring expansion; Selenium

Saturated NHC-stabilized borenium, boronium, hydride-bridged boron cations, and a bora-acyl chloride - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (ORGANOMETALLICS, 2024)
Keywords: activation; BORINIUM; Chemistry

Reactions of saturated NHC·boranes with electron-deficient alkynes and alkenes. borirane formation, their reactivities, and coupling of tetracyanoethylene - Amrutha, P. R.; Kundu, Gargi; Ganesh, Vemuri Lakshmi; Gonnade, Rajesh G.; Gopakumar, Gopinadhanpillai; Sen, Sakya S. (Dalton Transactions, 2026)
In this study, we describe the reactions of five- and six-membered saturated N-heterocyclic carbene boranes (NHC & centerdot;BH3) with electron-deficient alkenes and alkynes. Notably, both five- and six-membered saturated NHCs form boriranes upon the reaction of NHC & centerdot;BH3 with dimethyl acetylene dicarboxylate (DMAD). However, their reactivity with HCl differs: the five-membered saturated NHC-stabilized borirane undergoes ring opening in toluene/THF, whereas the six-membered saturated NHC-stabilized borirane undergoes ring expansion, forming exclusively a boralactone irrespective of solvent. Interestingly, when acetonitrile is used as a solvent, the five-membered saturated NHC-stabilized borirane yields both ring-opening and ring-expansion products. To remove the hydrogen attached to the boron atom in boriranes, we reacted the five-membered saturated NHC-stabilized borirane with AlCl3 and B(C6F5)(3), resulting in azaborolium cation or adduct formation, respectively. Transitioning from an electron-deficient alkyne to an alkene, the reaction of six-membered saturated NHC & centerdot;BH3 with tetracyanoethylene (TCNE) led to the unusual coupling of two TCNE molecules.